Controlling the Lateral Size and Excitonic Properties of Colloidal PbS Nanosheets. Issue 5 (21st January 2020) - Premathilaka, Shashini M.; Tang, Yiteng; Jiang, Zhoufeng; MDS Weeraddana, Tharaka; Debnath Antu, Antara; Bischoff, Seth; Sun, Liangfeng
Abstract: By changing the precursor lead‐to‐sulfur molar ratio in the synthesis of colloidal PbS nanosheets, the lateral size of the nanosheet can be tuned in a wide range from 100 nm to 1500 nm while keeping its thickness around 2.4 nm. Using chloroalkane molecules with a long carbon‐chain as the capping ligands can further reduce the lateral size down to 20 nm. The concentration of the chloroalkane in the reaction solution and the reaction temperature also have significant effects on the lateral size. At room temperature, nanosheets with a small lateral size exhibit a narrow light‐emission linewidth. The same nanosheets also show a sharp exciton peak near the band edge in the optical absorption spectrum. Abstract : The lateral size of the colloidal PbS nanosheets can be tuned in a broad range during the synthesis by changing the ratio of the precursors, the length and the concentration of the chloroalkane cosolvent. The excitonic properties (such as the exciton binding energy, the emission linewidth and lineshape) of the nanosheet are well revealed as the lateral size decreases.